2009
DOI: 10.1111/j.1524-4725.2009.01342.x
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Alar Necrosis Associated with Dermal Filler Injection

Abstract: Nasal alar necrosis associated with dermal filler injection is a rare event. Proper technique and recognition of risk factors may reduce the incidence of this complication. Physicians should be aware of early intervention and treatment options should impending necrosis become apparent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
93
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(95 citation statements)
references
References 25 publications
1
93
0
1
Order By: Relevance
“…Ischemia with subsequent skin necrosis mainly occurs in the glabella [6,7], nose [7][8][9][10][11][12], forehead [7,8], nasolabial fold [10], and cheek [13]. Moreover, intracranial artery embolism can lead to blindness caused by retinal artery occlusion and [10,11,13] has been sporadically reported to treat HA embolism-induced skin necrosis [14][15][16][17], however, well-designed case-control studies are required to verify the efficacy and safety of hyaluronidase before it can be used routinely in humans. Because HA injection-induced embolism is a rare complication, creation of an animal model is necessary for thorough study of its pathophysiological progress and potential treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Ischemia with subsequent skin necrosis mainly occurs in the glabella [6,7], nose [7][8][9][10][11][12], forehead [7,8], nasolabial fold [10], and cheek [13]. Moreover, intracranial artery embolism can lead to blindness caused by retinal artery occlusion and [10,11,13] has been sporadically reported to treat HA embolism-induced skin necrosis [14][15][16][17], however, well-designed case-control studies are required to verify the efficacy and safety of hyaluronidase before it can be used routinely in humans. Because HA injection-induced embolism is a rare complication, creation of an animal model is necessary for thorough study of its pathophysiological progress and potential treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Paucity of collateral circulation of vascular supply in glabella makes it vulnerable to tissue necrosis. The nature of heavy bleeding druing filler injection and acute onset of skin lesion were conclusive clues to a skin necrosis caused by hyaluronic acid as presented in this case [2].…”
Section: Sirmentioning
confidence: 88%
“…Practitioners and patients alike can take several steps to reduce the risk of contusion, but little is known about how to reduce the risk of vascular compromise. One of our studies suggested that prior blepharoplasty may increase the risk of developing vascular compromise (Grunebaum et al 2009 ). It is important to know how to recognize the warning signs of vascular compromise and communicate these descriptions to patients so that they will know when to present for immediate therapy to prevent progression and possible permanent scarring ( Fig.…”
mentioning
confidence: 95%
“…Among them, bruising is by far the most common but necrosis due to vascular occlusion is the most serious (Grunebaum et al 2009 ). Practitioners and patients alike can take several steps to reduce the risk of contusion, but little is known about how to reduce the risk of vascular compromise.…”
mentioning
confidence: 99%